Ocean waves across the Arctic: Attenuation due to dissipation dominates over scattering for periods longer than 19 s - Fabrice Ardhuin; Peter Sutherland; Martin Doble; Peter Wadhams (Geophysical Research Letters)
Abstract The poorly understood attenuation of surface waves in sea ice is generally attributed to the combination of scattering and dissipation. Scattering and dissipation have very different effects on the directional and temporal distribution of wave energy, making it possible to better understand their relative importance by analysis of swell directional spreading and arrival times. Here we compare results of a spectral wave model—using adjustable scattering and dissipation attenuation formulations—with wave measurements far inside the ice pack. In this case, scattering plays a negligible role in the attenuation of long swells. Specifically, scattering‐dominated attenuation would produce directional wave spectra much broader than the ones recorded, and swell events arriving later and lasting much longer than observed. Details of the dissipation process remain uncertain. Average dissipation rates are consistent with creep effects but are 12 times those expected for a laminar boundary layer under a smooth solid ice plate.